Integrating life cycle assessment and characterisation techniques: A case study of biodiesel production utilising waste Prunus Armeniaca seeds (PAS) and a novel catalyst - Al-Muhtaseb, Ala'a H.; Osman, Ahmed I.; Jamil, Farrukh; Mehta, Neha; Al-Haj, Lamya; Coulon, Frederic; Al-Maawali, Suhaib; Al Nabhani, Abdulrahman; Kyaw, Htet Htet; Myint, Myo Tay Zar; Rooney, David W. (Elsevier, 2021)
Prunus Armeniaca seed (PAS) oil was utilised as a waste biomass feedstock for biodiesel production via a novel catalytic system (SrO–La2O3) based on different stoichiometric ratios. The catalysts have been characterised and followed by a parametric analysis to optimise catalyst results. The catalyst with a stoichiometric ratio of Sr: La-8 (Sr–La–C) using parametric analysis showed an optimum yield of methyl esters is 97.28% at 65 °C, reaction time 75 min, catalyst loading 3 wt% and methanol to oil molar ratio of 9. The optimum catalyst was tested using various oil feedstocks such as waste cooking oil, sunflower oil, PAS oil, date seed oil and animal fat. The life cycle assessment was performed to evaluate the environmental impacts of biodiesel production utilising waste PAS, considering 1000 kg of biodiesel produced as 1 functional unit. The recorded results showed the cumulative abiotic depletion of fossil resources over the entire biodiesel production process as 22,920 MJ, global warming potential as 1150 kg CO2 equivalent, acidification potential as 4.89 kg SO2 equivalent and eutrophication potential as 0.2 kg PO43− equivalent for 1 tonne (1000 kg) of biodiesel produced. Furthermore, the energy ratio (measured as output energy divided by input energy) for the entire production process was 1.97. These results demonstrated that biodiesel obtained from the valorisation of waste PAS provides a suitable alternative to fossil fuels.
Keywords: SrO-La2O3; Synergistic effect; Prunus armeniaca seed oil; Waste biomass; Circular economy; Life cycle assessment